1985
DOI: 10.3382/ps.0640832
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sorbic Acid Feed Fungistat on the Intestinal Microflora of Floor-Reared Broiler Chickens

Abstract: The intestinal microflora of a group of broilers fed a diet containing .04% sorbic acid from Days 1 through 49 of their lives was compared with broilers given a diet without the fungistat. Four broilers from each group were killed at 7, 21, 35, and 49 days, and intestinal sections of the duodenum, the lower small intestine, and both ceca were removed aseptically. Samples of the contents of the intestinal sections were analyzed microbiologically. Groups of microorganisms analyzed included total aerobes, total a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…The antimicrobial role of OA is attributable to the capacity of their undissociated form to freely diffuse across the semipermeable cell membrane of the microorganism into the cytoplasm (Partanen and Mroz, 1999) where pH is near 7 and weak acids dissociate and depress the cellular enzymatic activity and nutrient transport system (Lueck, 1980). Sofos et al (1985) reported a reduction of coliforms count only in the duodenum of broilers fed diets supplemented with sorbic acid (0.04%). In our study similar results were observed in jejunum and cecum of PB-fed pigs, where the greater concentration of sorbic acid in PB than NPB could explain the lower plate counts of coliforms.…”
Section: Discussionmentioning
confidence: 97%
“…The antimicrobial role of OA is attributable to the capacity of their undissociated form to freely diffuse across the semipermeable cell membrane of the microorganism into the cytoplasm (Partanen and Mroz, 1999) where pH is near 7 and weak acids dissociate and depress the cellular enzymatic activity and nutrient transport system (Lueck, 1980). Sofos et al (1985) reported a reduction of coliforms count only in the duodenum of broilers fed diets supplemented with sorbic acid (0.04%). In our study similar results were observed in jejunum and cecum of PB-fed pigs, where the greater concentration of sorbic acid in PB than NPB could explain the lower plate counts of coliforms.…”
Section: Discussionmentioning
confidence: 97%
“…The medium (of 6 ml) roll-tube used for both culturing and counting the total anaerobes was FM 98-5 [23] . The plate media used were: MRS agar for Lactobacilli (Oxoid, England), Bifidobacteria agar for Bifidobacteri [24] , Brain Heart Infusion agar (BHIA) for total aerobic bacterial count, MacConkay agar (BBL) for Coliforms, and KF Streptococcus agar (DIFCO, USA) for Streptococci. All the inoculated rolltubes and plates were incubated at 39°C.…”
Section: Sampling Testing and Observationsmentioning
confidence: 99%
“…The most common mycotoxins are aflatoxins, ochratoxins, trichothecenes and zearalenone, which could be found in a wide spectrum of food, such as dry feed, cereals, cheese, coffee, corn, fruits, vegetables etc. The problem can be partially confronted with the use of fungal growth inhibitors, such as acetic acid, propionic acid, sorbic acid and its salts (Holley, 1981;Bartov, 1983;Sofos et al, 1985;Mahjoub and Bullerman, 1986;Skrinjar et al, 1995), as well as with the use of carbamates, organophosphorus and organochlorine insecticides (Britt et al, 1974;Windstrom et al, 1976;Draughon et al, 1983).…”
Section: Introductionmentioning
confidence: 99%